2004
DOI: 10.1143/jjap.43.6740
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thin-Film Decoupling and High-Frequency (Ba,Sr)TiO3 Capacitors on Al2O3 Ceramic Substrates

Abstract: In this paper we present the results of the characterization of parallel-plate thin-film (Ba1-x ,Sr x )TiO3 (BST) capacitors, to demonstrate their suitability for use as decoupling capacitors (a capacitance as high as 0.34 µF and a capacitance density of up to 70 fF/µm2) and as tunable RF components (a small capacitance from 0.5 pF to 16 pF, a high tunability of 4.22:1 at 10 V and a capacitance density of up to 34 fF/µm2). BST films of different composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The application as tunable devices for telecommunications which are operated in the microwave range ͑300 MHz to 300 GHz͒ requires detailed knowledge of the microwave properties in the high-frequency domain. 7,8 Although ferroelectric materials in thin-film form often show inferior properties as compared to bulk ceramics, it has been demonstrated that high quality epitaxial films generally have much better properties than polycrystalline films. [9][10][11] Very recently, it was shown that by depositing epitaxial ͑111͒-oriented BST films on Al 2 O 3 ͑0001͒ substrates, it is possible to obtain higher tunability while keeping the microwave loss low compared to polycrystalline BST films.…”
mentioning
confidence: 99%
“…The application as tunable devices for telecommunications which are operated in the microwave range ͑300 MHz to 300 GHz͒ requires detailed knowledge of the microwave properties in the high-frequency domain. 7,8 Although ferroelectric materials in thin-film form often show inferior properties as compared to bulk ceramics, it has been demonstrated that high quality epitaxial films generally have much better properties than polycrystalline films. [9][10][11] Very recently, it was shown that by depositing epitaxial ͑111͒-oriented BST films on Al 2 O 3 ͑0001͒ substrates, it is possible to obtain higher tunability while keeping the microwave loss low compared to polycrystalline BST films.…”
mentioning
confidence: 99%
“…The films obtained were annealed at 500 C in atmospheric O 2 flow for 30 min. Epitaxial SrRuO 3 films 100 nm thick were deposited on (100) and 111 7,13) The crystal structure of the films was characterized by X-ray diffraction (XRD). The composition of the films was ascertained using a wavelength dispersion X-ray fluorescence (XRF) spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Barium strontium titanate perovskites along the barium to strontium solid solution have been extensively studied due to their interesting electrical properties. In the case of thin films, studies have focused on material compositions, synthetic routes, and the influence of the substrate. The main applications of such materials are decoupling capacitors, as well as their potential use in tunable microwave applications.…”
Section: Introductionmentioning
confidence: 99%